CULTURAL AND POLITICAL IMPLICATIONS IN RUNAWAY TO NOWHERE BY QASHAM ALI BALATA - ALHAMID, LOLAV MOHAMMED HASSAN; ABDULQADIR, DILAN NADIR (Journal of Duhok University, 2020)
ABSTRACT Edith Hamilton, the famous German-American educator and author, once said that “A people’s literature is the great textbook for real knowledge of them. The writings of the day show the quality of the people as no historical reconstruction can.” Hamilton’s saying appropriately applies on Qasham Ali Balata’s novel Runaway to Nowhere. This research study aims at the exploration of the closer considerations to the cultural and political references in the novel, which are found in every single page of the book. The observations will be documented through quotations from the novel. The study starts with an introduction to the novel intending to familiarize the reader with the story and the characters. The first section (cultural references) deals with regional considerations; including the regional demography, language, cuisine, and the national costumes of the Kurdish people. The Kurdish folklore, with some of its tales and legends are also discussed. This section ends with the discussion of social themes; containing critical issues like the role of the Kurdish woman in society and socialization in the Kurdish community. The second section describes the political references, which are ordered logically. Starting from the geopolitical importance of Kurdistan, that moves Kurdistan into the focus of their imperialistic neighbors. The novel limits itself to Iraqi- Kurdistan; thus, only the oppressions of the regime in Baghdad are discussed. The Iraqi Kurdish resistance is explained as well as the sanctions of the occupiers of Iraqi Kurdistan, the Iraqi regimes in Baghdad, in particular the Ba’ath- party. The focus lies on the latter mentioned party, who is responsible for the sequence of wars and mass murders against other nations or their own citizens, in particular the Iraqi Kurds.